2011
DOI: 10.1103/physrevb.84.134107
|View full text |Cite
|
Sign up to set email alerts
|

Relative phase stability and lattice dynamics of NaNbO3from first-principles calculations

Abstract: We report total energy calculations for different crystal structures of NaNbO 3 over a range of unit cell volumes using the all-electron full-potential (L)APW method. We employed both the local-density approximation (LDA) and the Wu-Cohen form of the generalized gradient approximation (GGA-WC) to test the accuracy of these functionals for the description of the complex structural behavior of NaNbO 3 . We found that LDA not only underestimates the equilibrium volume of the system but also predicts an incorrect … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Although great effort has been devoted to understand the fundamental mechanism of the phase transitions observed in NaNbO 3 using first principle calculations [21][22][23][24][25], we still have little knowledge due to presence of several competing structural instabilities with very similar free energies. Theoretically, we can predict the transition pressure by plotting the free energy as a function of pressure for various phases and identifying the phases of minimum free energy.…”
Section: Resultsmentioning
confidence: 99%
“…Although great effort has been devoted to understand the fundamental mechanism of the phase transitions observed in NaNbO 3 using first principle calculations [21][22][23][24][25], we still have little knowledge due to presence of several competing structural instabilities with very similar free energies. Theoretically, we can predict the transition pressure by plotting the free energy as a function of pressure for various phases and identifying the phases of minimum free energy.…”
Section: Resultsmentioning
confidence: 99%
“…As has been shown recently for oxide semiconductors, this might improve with a self-consistent determination of the amount of Hartree-Fock exactexchange mixed into the hybrid functional [20]. However, as already mentioned by Machado et al [15], it is not correct to directly compare the high-temperature measurements of the simple cubic perovskite Pm3m phase with the zerotemperature DFT calculations.…”
Section: Simple Cubic Perovskite Pm3mmentioning
confidence: 98%
“…Diéguez et al [13] reported a first-principle study of epitaxial strain in perovskites, including KNbO 3 and NaNbO 3 , while Li et al [14] reported density functional theory (DFT) calculations for epitaxially strained KNbO 3 /NaNbO 3 superlattices, thereby including the unstrained simple cubic perovskite phase (Pm3m) as well. Finally, Machado et al [15] reported on the relative phase stability and lattice dynamics of NaNbO 3 from first principles. A rigorous assessment of the performance of different exchange-correlation functionals within DFT calculations and applied to the possible crystalline phases of NaNbO 3 at room temperature and below is still missing to date.…”
Section: Introductionmentioning
confidence: 99%
“…53 These instabilities are very common in cubic perovskites and were very well studied. [54][55][56] Having established the phonon instabilities of the ideal cubic phase we now present the outcomes of our structural search, which is based on the stabilization of the negative phonon modes through suitable atomic displacements.…”
Section: A Phonon Dispersion Of Cubic Phasementioning
confidence: 99%